2018
DOI: 10.1186/s12944-018-0728-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in MALAT1 with risk of coronary atherosclerotic heart disease in a Chinese population

Abstract: BackgroundMetastasis associated lung adenocarcinoma transcript 1 (MALAT1) plays an important role in vascular remodeling. Down-regulation of MALAT1 can inhibit the proliferation of vascular endothelial cells and vascular smooth muscle cells, reduce cardiomyocyte apoptosis and improve left ventricular function, which is closely linked to numerous pathological processes such as coronary atherosclerotic heart disease (CAD). The aim of this study was to investigate whether polymorphisms in MALAT1 were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 38 publications
3
50
1
Order By: Relevance
“…38 The SNPs in MALAT1 were associated with CVD risk in a Chinese population. 39 MALAT1 was also found up-regulated in patients with unstable angina and high-fat food fed ApoE −/− mice, indicating MALAT1 participated in development of atherosclerosis. 35,40 Knockdown of MALAT1 caused increased plaque size and infiltration of inflammatory CD45 + cells partly via regulation of miR-503.…”
Section: Malat1 and Atherosclerosismentioning
confidence: 90%
See 1 more Smart Citation
“…38 The SNPs in MALAT1 were associated with CVD risk in a Chinese population. 39 MALAT1 was also found up-regulated in patients with unstable angina and high-fat food fed ApoE −/− mice, indicating MALAT1 participated in development of atherosclerosis. 35,40 Knockdown of MALAT1 caused increased plaque size and infiltration of inflammatory CD45 + cells partly via regulation of miR-503.…”
Section: Malat1 and Atherosclerosismentioning
confidence: 90%
“…Atherosclerosis is the main cause of CVD . The SNPs in MALAT1 were associated with CVD risk in a Chinese population . MALAT1 was also found up‐regulated in patients with unstable angina and high‐fat food fed ApoE −/− mice, indicating MALAT1 participated in development of atherosclerosis .…”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 93%
“…In recent years, increasing evidence has indicated that lncRNAs play 24 or coronary atherosclerotic heart disease. 25 We found that the MALAT1 rs664589 C>G polymorphism was significantly associated with increased endometrial cancer risk.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Wu et al (2019) showed that SNPs of the MALAT1 rs664589 polymorphism inhibit the binding of miR-194-5p, leading to the increased risk of colorectal cancer. Wang et al (2018) found that rs619586 locus of the MALAT1 is associated with the risk of coronary atherosclerotic heart disease. In this study, we found that the SBP and DBP of the G allele carriers of the rs664589 locus of the MALAT1 gene were significantly higher than those of the C allele carriers, and the G allele gene was susceptible for hypertension.…”
Section: Discussionmentioning
confidence: 99%